Antibacterial effect of a disinfectant spray for sports mouthguards on Streptococcus sobrinus - Gen Tanabe; Hiroshi Churei; Yasuo Takeuchi; Kairi Hayashi; Aki Kanasaki; Yuriko Yoshida; Jun Toma; Yosiaki Araie; Toshiaki Ueno (Wolters Kluwer Medknow Publications, 2021)
Background: Mouthguard (MG) disinfectant sprays are available for maintaining MG hygiene. The effect of these sprays against Streptococcus sobrinus is still unknown. The purpose of this study was to evaluate the antibacterial effect of an MG disinfectant spray against S. sobrinus using the modified ISO 22196 standard. Materials and Methods: In this in vitro study, we used the following treatment groups for antibacterial testing: MG spray-1 (left in spray for 30 s), MG spray-2 (60 s), and control (n = 4). All analyses were performed at a statistically significant level (P = 0.05) using JMP® 14. Results: The log colony-forming units of the MG spray-2 group were significantly lower than those of the other groups. The antibacterial activity of MG spray-2 against S. sobrinus was >2.1. Conclusion: We confirmed the antibacterial effect of the MG spray against S. sobrinus, and it was influenced by the treatment duration, with the optimum effect at a longer duration.